KEDAULATAN NEGARA VS TANGGUNG JAWAB NEGARA DALAM UPAYA PERLINDUNGAN LINGKUNGAN GLOBAL - Isnaeni, Nurul (Global: Jurnal Politik Internasional, 2004)
The dominance of the concept of sovereignty has been challenged in the term of international environmental relations. The development of issues with its transboundary character is one of the challenger. Normatively and empirically, the concept of sovereignty, which refers to a state's right to, inter alia, exploit its natural resources, has now been challenged by the concept of state responsibility, which refers to the state's obligation to manage the sustainability of its resources. This can be seen in various international environmental regimes. Though, the principles in the regimes are of softer status that they do not create substantive obligations that are actionable in their own right.